(–)-Epigallocatechin-3-Gallate Ameliorates Atherosclerosis and Modulates Hepatic Lipid Metabolic Gene Expression in Apolipoprotein E Knockout Mice: Involvement of TTC39B - Wang, Wei; Zhang, Zheng-Zhu; Wu, Yan; Wang, Ru-Qing; Chen, Jin-Wu; Chen, Jing; Zhang, Yan; Chen, Ya-Jun; Geng, Ming; Xu, Zhong-Dong; Dai, Min; Li, Jin-Hua; et al. (Frontiers in Pharmacology, 2018)
Background: Aberrant chronic inflammation and excess accumulation of lipids play pivotal role in the occurrence and progression of atherosclerosis. (-)-Epigallocatechin-3-gallate (EGCG), the major catechins in green tea, displayed anti-atherosclerotic properties in vivo and in vitro. However, the effects and underlying mechanism of EGCG on atherosclerosis remains unclear. Methods: Male apolipoprotein E-knockout (ApoE-/-) mice (7 weeks old) fed with high-fat diet were treated with normal saline or EGCG (40 mg/kg/d, i.g.) for 18 weeks. Atherosclerotic plaque and liver lipid accumulation were measured by oil red staining. Plasma lipids and cytokines were detected using commercial kits. The expression of protein and mRNA were analyzed by Western blot and quantitative real-time reverse transcription-polymerase chain reaction, respectively. Results: EGCG administration markedly attenuated atherosclerotic plaque formation in high-fat diet-fed ApoE-/- mice, which were accompanied by increased plasma interleukin-10 (IL-10) level and decreased plasma IL-6 and tumor necrosis factor-α (TNF-α) levels. In addition, EGCG modulated high fat-induced dyslipidemia, evidencing by decreased total cholesterol (TC) and low-density lipoprotein (LDL) levels and increased high-density lipoprotein (HDL) level. Meanwhile, EGCG treatment alleviated high fat-mediated liver lipid accumulation and decreased liver TC and total triglyceride. Mechanistically, EGCG significantly modulated high fat-induced hepatic tetratricopeptide repeat domain protein 39B (TTC39B) expression and its related genes (Lxrβ, Abcg5, Abcg8, Abca1, Elovl5, Srebf1, Scd1, Scd2, Fas, Elovl5, Mylip) expression in liver from ApoE-/- mice. Notably, EGCG remarkably induced hepatic liver X receptor α (LXRα) and LXRβ expression and inhibited both precursor and mature sterol regulatory element binding transcription factor-1 (SREBP-1) expression. Conclusion: Taken together, our data for the first time suggested that TTC39B was involved in EGCG-mediated anti-atherosclerotic effects through modulation of LXR/ SREBP-1 pathway.